Analysis of insulin and insulin analogs from dried blood spots by means of liquid chromatography–high resolution mass spectrometry. Issue 11 (8th November 2018) - Thomas, Andreas; Thevis, Mario
Abstract: While dried blood spot (DBS) analysis concerning low molecular mass molecules has become more and more established in various fields of analytical chemistry, the utility of DBS in determining peptides and proteins from DBS is yet comparably limited. In consideration of the fact that the apparent benefits of DBS sampling are similar for analytes of lower and higher molecular mass, dedicated (non‐generic) sample preparation procedures are required that meet the needs for detecting peptidic drugs and hormones in DBS. The analysis of insulin and its synthetic analogs by mass spectrometry has received increased attention in several fields such as doping controls, forensics, and drug metabolism and pharmacokinetics studies. Hence, a strategy facilitating the analysis of insulin and its synthetic or animal analogs (human, Lispro, Aspart, Glulisine, Glargine, Detemir, Tresiba, and porcine and bovine insulin) from DBS was developed. The successful analysis of these substances at physiologically relevant concentrations was realized after ultrasonication‐assisted extraction, immunoaffinity purification, and liquid chromatographic separation followed by high resolution mass spectrometric detection (with or without ion mobility). Assay validation demonstrated adequate sensitivity (LOD 0.5 ng/mL for most insulins), as well as precise (< 25%) and reproducible results for all included target insulins. Additionally, proof‐of‐principle data were obtained by the analysis of DBS samples obtained from healthy volunteers in non‐fasting state as well as a sample from a diabetic volunteer treated with the fast acting analog insulin Aspart. Abstract : Sensitive analysis of insulin and its analogues from Dried Blood Spots by means of LC‐HRMS after immunoaffinity purification at physiological and pharmacological relevant levels (LOD: 0.5 ng/mL) is enabled within this study. The method was validated and applied to real post administration samples.